The Effect of Profit Growth, Capital Structure, and Investment Opportunity Set on Profit Quality with Firm Size as a Moderating Variable (Empirical Study of Manufacturing Companies in the Consumption Goods Industry Sector Listed on the IDX in 2017 – 2021) - Maryati Maryati; Muhyarsyah Muhyarsyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study is to empirically test the effect of profit growth, capital structure, and investment opportunity sets on earnings quality which is moderated by company size in manufacturing companies in the consumer goods sector listed on the IDX from 2017 to 2021. Purposive sampling was used in the sample selection method of this study with the sample obtained, namely 26 companies with a total of 130 data observations. Panel regression data analysis in statistical calculations with the help of Eviews12 was used in this study. Based on the results of the output of Eviews12 the conclusion of the hypothesis test stated that profit growth and capital structure do not affect earnings quality. While the investment opportunity set affects the quality of earnings. After being moderated by company size, the results show that company size is not proven to moderate the effect of profit growth and capital structure on earnings quality, while company size is proven to be able to moderate the effect of investment opportunities on earnings quality.